The Role of Six1 in Transcriptional Regulation during Myogenesis - Liu, Yubing (Université d'Ottawa / University of Ottawa, 2017)
Skeletal myogenesis is under the control of a combinatorial network of transcription factors. It has been shown that the homeobox protein Six1 is required for embryonic myogenesis. Using functional genomics approaches, I determined that Six1 is required for myoblasts differentiation through direct binding to a cluster of genes that are related to muscle function and muscle structure during my Master’s studies. However, it was still not fully understood how Six1 selects its genomic targets and whether Six1 regulates the expression of Myod directly. I devoted my PhD work to study three central aspects of Six1 function: through what DNA motif it binds to DNA, how it regulates the expression of the myogenic regulatory factor MyoD, and how it might regulate chromatin structure at the enhancer regions of muscle genes. A more degenerate MEF3-like DNA sequence consensus has been identified from Six1 ChIP-on-chip experiments. This MEF3 motif was further optimized using bioinformatic methods and was proved to discover Six1 binding sites with improved specificity and sensitivity. Myod, a member of myogenic regulatory factors (MRFs), is a master regulator in the myogenic lineage. Multiple MEF3 sites were identified on the regulatory regions of Myod, including two MEF3 sites within its core enhancer region (CER). Six1 was able to bind to the CER directly through these two MEF3 sites and regulated the Myod expression in cultured primary myoblasts. Previous work has suggested that the CER is also bound by Myod in myoblasts. I demonstrated that the binding of Myod to the CER depended on the presence of Six1. Six1 was also involved in maintaining a relatively ‘open’ chromatin structure at the CER, suggesting that Six1 may play a direct or indirect role in chromatin remodeling. During my Master’s studies, I demonstrated a synergistic regulation by the Six and MRF families. This synergistic function gains potential importance by the fact that ~25% of Six1 genomic targets are also bound by Myod. I decided to study whether the co-occupancy of Six1 and Myod was essential to maintain the proper global chromatin structure at these loci. Six1 and Myod co-bound genomic regions correlated with more accessible chromatin, which was detected by the formaldehyde-assisted isolation of regulatory elements (FAIRE) assay followed by DNA deep sequencing (FAIRE-seq). When combined with small interfering RNA-mediated gene knockdown of Six1 or Myod, FAIRE-seq data suggested that Six1, but not Myod, was involved in regulating the chromatin accessibility at these co-bound DNA loci. To shed light on the mechanism by which Six1 functions, proteomics approaches were used and revealed that proteins involved in “regulation of transcription” and “chromatin organization” were enriched among Six1-bound proteins. Cdk9 and its partner cyclin T have been shown to stimulate gene expression by releasing RNA polymerase II from transcriptional pause, but they can also function at gene enhancers. I determined that Six1 and Cdk9 participated in the same protein complex, and that the Cdk9 activity appeared to mediate the effect of Six1 on the chromatin accessibility at the CER to regulate the Myod expression. Taken together, these results demonstrate that Six1 regulates the expression of Myod through its direct binding on the CER which facilitates transcriptional elongation.
Keywords: Six1; Myod; Myogenesis; transcription; MEF3 DNA motif; Cdk9